2018
DOI: 10.1111/age.12712
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding MEG3 is a marker for skeletal muscle development and meat production traits in pigs

Abstract: Long non-coding RNA maternally expressed gene 3 (lncRNA MEG3) plays an important role in mammalian muscle development. Our previous transcriptome study showed that lncRNA MEG3 is differentially expressed during postnatal skeletal muscle development in pigs. The objective of the present study was to analyse the role of lncRNA MEG3 in prenatal and postnatal skeletal muscle development and investigate the association of MEG3 with meat production traits in pigs. We investigated the sequence conservation and tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…Intriguingly, our data showed that the expression levels of Gtl2 and IG-DMR were increased in two muscle hypertrophy models and were decreased in multiple muscle atrophy models. We and others previously found that the expression levels of lncRNAs at this locus are gradually decreased during muscle growth and aging in mice and pigs [36,[69][70][71]. It is of note that the level of DUM1 expression, which was correlated with the skeletal muscle mass in this study, also gradually decreased during muscle growth and aging in mice [29].…”
Section: Discussionsupporting
confidence: 72%
“…Intriguingly, our data showed that the expression levels of Gtl2 and IG-DMR were increased in two muscle hypertrophy models and were decreased in multiple muscle atrophy models. We and others previously found that the expression levels of lncRNAs at this locus are gradually decreased during muscle growth and aging in mice and pigs [36,[69][70][71]. It is of note that the level of DUM1 expression, which was correlated with the skeletal muscle mass in this study, also gradually decreased during muscle growth and aging in mice [29].…”
Section: Discussionsupporting
confidence: 72%
“…Longissimus dorsal muscles of embryonic pigs (Yu et al, 2018). Similar to the tissue expressions of postnatal Day 160 in Large White pigs, lncRNA-MEG3 was also highly expressed in skeletal muscle and showing lncRNA-MEG3 was conserved and expressed in many tissues in human (Zhang et al, 2010).…”
Section: And the Expression Pattern Inmentioning
confidence: 75%
“…Here we identified, for the first time to our knowledge, a sow prolificacy-associated variant, 19-bp duplication in the promoter region of lincRNA NORFA. In domestic animals, only a few lncRNA variants associated with important economic traits were found, including variants rs325797437, rs344501106, rs81286029, and rs318656749 in lncRNA MEG3 associated with porcine meat production traits 62 , a variant g.1263T>A in lncRNA ADNCR associated with bovine growth traits 63 , and a variant in lincRNA GDNF-AS associated with canine insensitivity to pain 64 . Overall, based on the distribution of the 19-bp duplication in pig breeds with different fertility and the expression levels of NORFA in granulosa cells from individuals with different genotypes, we identified for the first time that a candidate lincRNA for sow prolificacy, providing insights into the molecular mechanism of the high prolificacy of Erhualian pigs.…”
Section: Discussionmentioning
confidence: 99%